Evaluating a multifaceted stewardship intervention on proton pump inhibitor utilization: an interrupted time-series analysis of prescribing patterns in a northwest Chinese hospital - Wang, Xiaoling; McIver, David J.; Min, Hui; Guo, Jia; Li, Haiyan (Frontiers in Pharmacology, 2026)
BackgroundPromoting the rational use of proton pump inhibitors (PPIs) has become an important aspect in controlling the growth of pharmaceutical expenditures in China. In recent years, the first national guidelines for the clinical application of PPIs and the second batch of the China National Key Monitoring Drug (NKMD) policy were released to regulate PPI utilization. However, few studies have fully investigated the impact of the multifaceted stewardship intervention on PPI utilization in hospitals, especially in northwestern China.MethodsWe collected monthly PPI usage data over 8 years from a tertiary hospital of northwestern China between January 2017 and December 2024. Multi-intervention interrupted time-series (ITS) analysis was used to evaluate the change in the defined daily dose (DDD) per 100 bed-days under the intervention measures managed by clinical pharmacists through the multifaceted stewardship.ResultsAlthough the DDD per 100 bed-days for overall PPIs decreased by 12.93 (p = 0.009) under the national guidelines (intervention1), no significant time trend in the overall PPI utilization was observed (p = 0.603). However, following the implementation of the NKMD policy (intervention2), a significant decreasing trend (β4 = −0.46, p = 0.011) emerged in the DDD per 100 bed-days for overall PPIs. The national guidelines (intervention1) led to significant immediate reductions in both oral (β1 = −5.67, p = 0.005) PPI consumption and intravenous (β1 = −7.26, p = 0.020) PPI consumption. However, the trend for oral PPIs subsequently exhibited a significant upward slope (β2 = 0.26, p = 0.015) under the national guidelines (intervention1). Conversely, the consumption of oral PPIs showed a significant sustained linear decreasing trend (β4 = −0.58, p < 0.001) under the NKMD policy (intervention2).ConclusionThe implementation of the national guidelines led to a significant immediate reduction, but no significant time trend in the overall PPI utilization was observed. Our findings highlight the impact of the NKMD policy on the sustained downward trend in overall and oral PPI consumption. The prospective prescription review system may be effective in promoting the long-term rational use of PPIs in clinical practice.